Genomic investigation of a non-travel Plasmodium falciparum case linked to imported malaria in China’s post-elimination era - Fei Luo; Dan Jiang; Jing-Ru Xu; Yan Tan; Meng-Ping Yang; Jun Xie; Sen-Ping Yang; Hai-Mo Shen; Shuang Zhou; Jun-Hu Chen (Malaria Journal)
Abstract Background Although China has achieved malaria elimination, the risk of reintroduction persists due to imported Plasmodium falciparum cases. Occasional infections without a clear travel history present challenge to routine epidemiological investigation and underscore the need for advanced tracing tools. Methods Whole-genome sequencing (WGS), principal component analysis (PCA), and identity-by-descent (IBD) analysis were applied to investigate a P. falciparum case reported in Chongqing, China, in 2019. The patient had no overseas travel history but was treated at the same hospital with a confirmed imported case from the Democratic Republic of the Congo (DRC). Results Genomic analysis placed the unidentified case within the West and Central African parasite cluster. IBD analysis showed a high degree of relatedness (IBD = 0.9) between this case and the DRC-imported case, suggesting a potential transmission link. These findings indicate the likely Central African origin of the infection and raise concerns about local transmission risk even in a post-elimination setting. Discussion This case highlights the limitations of traditional epidemiology in detecting cryptic transmission routes. Genomic epidemiology enables finer-scale resolution of parasite origin and relatedness, providing critical evidence in elimination-phase malaria control. Conclusions Genomic tools such as WGS, PCA, and IBD analysis can enhance national malaria surveillance systems by identifying infection sources and clarifying transmission routes. Their integration supports elimination-stage strategies and helps prevent malaria reintroduction in formerly endemic regions.